Consuming Fiction: Stories about Consumerism, Shopping and Consumption - Kaela Jubas (Adult Education Research Conference, 2007)
From a critical cultural studies perspective, this paper acknowledges the tension between culture and materiality, and asserts that opportunities for informal, critical adult learning are present in everyday life. It uses consumerism as an example of hegemonic ideology encountered in daily living, and presents two anti-hegemonic responses to it.